Identification and functional clustering of global gene expression differences between age-related cataract and clear human lenses and aged human lenses - Hawse, J.R.; Hejtmancik, J.F.; Horwitz, J.; Kantorow, M. (Experimental eye research, 2004)
We have examined the gene expression profiles of young, old and cataractous human lenses in order to differentiate those gene expression changes specific for cataract from those also associated with lens aging. Differentially expressed transcripts were identified by oligonucleotide microarray analysis and clustered according to their known functions. Four hundred and twelve transcripts that are increased and 919 transcripts that are decreased were identified at the 2-fold or greater level between epithelia isolated from cataract relative to clear lenses while 182 transcripts that are increased and 547 transcripts that are decreased were identified at the 2-fold or greater level between young and old lens epithelia. Comparison of the cataract gene expression changes with those detected in lens aging revealed that only 3 transcripts exhibited similar trends in gene expression. These data suggest that cataract- and age-specific changes in gene expression do not overlap and provide evidence for multiple cataract- and age-specific gene expression changes in the human lens.